Following the breadcrumbs: An analysis of online product review characteristics by online shoppers. Issue 2 (4th March 2017) - Muralidharan, Sidharth; Yoon, Hye Jin; Sung, Yongjun; Miller, Jessica; Lee, Arturo
Abstract : Consumer-generated product reviews are a driving force behind online purchases; at the same time, unfavorable reviews can discourage interested online shoppers and eventually hurt the brand. The objective of this exploratory study was to analyze a diverse range of characteristics and the valence of online product reviews that would aid in responding to customer dissatisfaction. Product reviews ( N  = 1982) fromAmazon.com were collected and content analyzed. Some of the key findings include the following: (a) price was the most commonly discussed product feature; (b) online shoppers found two-sided reviews to be most informative, contradicting the commonly held assumption that negative reviews were more informative and diagnostic in nature; and (c) 'no action' was the most common end action across two-sided and negative reviews, indicating that varying levels of dissatisfaction might not always lead to a negative end action. Implications for marketers are discussed.